Re‐evaluation of glycerol esters of wood rosin (E 445) as a food additive. (26th July 2018) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Filipič, Metka; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; Lambré, Claude; et al.
Abstract: The present opinion deals with the re‐evaluation of glycerol esters of wood rosin (GEWR, E 445) when used as a food additive. Regarding GEWR originating from Pinus palustris (longleaf pine) and Pinus elliottii (slash pine), based on the overall toxicity database, and given the absence of reproductive and developmental toxicity data, the Panel concluded that the current acceptable daily intake (ADI) of 12.5 mg/kg body weight (bw) per day for GEWR (E 445) as established by the Scientific Committee on Food (SCF) in 1994 should be temporary pending the provision of such data. This assessment is restricted to GEWR derived from P. palustris (longleaf pine) and P. elliottii (slash pine) and with a chemical composition in compliance with GEWR used in the toxicological testing. The Panel concluded that the mean and the high exposure levels (P95) of the brand‐loyal refined exposure scenario did not exceed the temporary ADI in any of the population groups from the use of GEWR (E 445) as a food additive at the reported use levels. For GEWR originating from Pinus halepensis and Pinus brutia, the Panel noted that concentrations of the fractions of 'glycerol monoesters', 'free resin acids' and 'neutrals', which are considered to be of particular toxicological relevance, are not known; therefore, the evaluation of chemical equivalence with GEWR originating from P. palustris (longleaf pine) and P. elliottii (slash pine) is not possible; no data on stability were available; no toxicological data were available. Therefore, the Panel concluded that a safety assessment of GEWR originating from P. halepensis and P. brutia could not be performed. The Panel recommended the European Commission to consider an update of the definition of GEWR (E 445) in the EU specifications. It should be indicated that GEWR (E 445) (i) contain, besides the mentioned glycerol di‐ and triesters, a residual fraction of glycerol monoesters, and (ii) contain residual free resin acids and neutrals (non‐acidic other saponifiable and unsaponifiable substances).